The Effect of 3 Months Kb Injection with Changes in Menstrual Cycle at Pmb Hanifatuz Zakiyah Kandang Tepus Senduro Lumajang Undergraduate Midwifery Study Program Stikes Hafshawaty Zainul Hasan Genggong Probolinggo - Zzaqia, Hanifatu; Wahyuningsih, Sri; Widyati, Agustina (NHM PRESS, 2023)
Population growth is a global problem that arises in the world, especially developing countries. Indonesia is the fourth country with the largest population in the world and is one of the countries with the fastest population growth rate in the world. Contraception is an effort to prevent pregnancy so that it is expected to reduce the high birth rate, but the contraception given cannot be separated from the name side effects, this makes it not an easy thing to use contraception. The purpose of this study was to analyze the effect of 3-month birth control injections with changes in the menstrual cycle at Pmb Hanifatuz Zakiyah Kandang Tepus, Senduro Lumajang. The design of this study uses a correlative observational design with a Cross Sectional approach. The sampling technique in this study uses non-probability sampling. The questionnaire used is the menstrual disorder questionnaire. Correlative test results show a p value of 0.000 (α < 0.05) which means Ha is accepted where there is an influence between 3-Month Kb Injections and Changes in the Menstrual Cycle at Pmb Hanifatuz Zakiyah in theory DMPA can inhibit implantation. Depo Provera injection contraception works, namely: Blocking the release of FSH and LH so that ovulation does not occur. This imbalanced hormonal condition will affect the mother's menstrual cycle.